2003
DOI: 10.1523/jneurosci.23-03-00766.2003
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Hippocampal Spreading Depression and Enhanced Locomotory Activity in Mice with Astrocyte-Directed Inactivation of Connexin43

Abstract: Using a human glial fibrillary acidic protein (hGFAP) promoter-driven cre transgene, we have achieved efficient inactivation of a floxed connexin43 (Cx43) gene in astrocytes of adult mice. The loss of Cx43 expression was monitored in a cell-autonomous manner via conditional replacement of the Cx43-coding region by a lacZ reporter gene. In this way, we bypassed the early postnatal lethality previously reported for Cx43 null mice and characterized the phenotypic consequences of Cx43 deficiency in the CNS. Mice l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
274
5
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 248 publications
(304 citation statements)
references
References 58 publications
(99 reference statements)
24
274
5
1
Order By: Relevance
“…Indeed, in the neocortex of embryonic Cx43-deficient mice, changes in migration of neurons have been observed, which were however fully compensated during later development (34). The overall brain architecture of newborn (35) and adult mice lacking Cx43 in astrocytes was normal (36). The DG of adult constitutive dko mice also looked roughly normal, although our BLBP stainings revealed a clear reduction of RG-like cells in the SGZ, which might well account for the decreased proliferation.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, in the neocortex of embryonic Cx43-deficient mice, changes in migration of neurons have been observed, which were however fully compensated during later development (34). The overall brain architecture of newborn (35) and adult mice lacking Cx43 in astrocytes was normal (36). The DG of adult constitutive dko mice also looked roughly normal, although our BLBP stainings revealed a clear reduction of RG-like cells in the SGZ, which might well account for the decreased proliferation.…”
Section: Discussionmentioning
confidence: 73%
“…The abolition of gap junctional communication has been shown to heighten neuronal vulnerability to various disturbances (Blanc et al, 1998;Naus et al, 2001;Ozog et al, 2002b). Furthermore, Cx expression, both dependent and independent of gap junctional communication, also has been shown to be protective against cellular injury (Siushansian et al, 2001;Lin et al, 2003;Nakase et al, 2003Nakase et al, , 2004Theis et al, 2003). These studies included the ubiquitous disruption of Cx43 expression as well as astrocyte-specific Cx43 knockout animal models.…”
Section: Discussionmentioning
confidence: 99%
“…These studies included the ubiquitous disruption of Cx43 expression as well as astrocyte-specific Cx43 knockout animal models. Specifically, Theis et al (2003) have identified that astrocytic-specific Cx43-deficient mice are characterized by increased spreading depression upon a CNS disturbance. Sohl et al (2000) have recognized that even a small decrease in astrocytic Cx43 can perturb proper spa- Plasmid pHXPL contained 6.7 kb of the murine Cx43 promoter inserted in front of a LacZ expression cassette.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cre-mediated recombination leading to loss of Cx43 expression could be monitored by X-Gal staining. 23 All mice were generated and genotyped 23 in the Institute of Genetics, University of Bonn, Germany.…”
Section: Conditional Knockout Micementioning
confidence: 99%
“…In this study, we used mice with astrocyte-directed ablation of Cx43 23 to analyze the neuroprotective role of astrocytic gap junctions in focal brain ischemia. In Cx43(ϩ/Ϫ) mice, Cx43 is compromised not only in astrocytes but also in many other cell types and organs, including the heart and vasculature.…”
mentioning
confidence: 99%